2009
DOI: 10.1177/0891242409347370
|View full text |Cite
|
Sign up to set email alerts
|

Education Spending and State Economic Growth: Are All Dollars Created Equal?

Abstract: This article contributes to the literature on the effect of state and local education spending on U.S. state economic growth by separately analyzing higher and K-12 education spending and by taking into account the possibility that education spending may generate spillover effects to neighboring states. Results from a series of fixed-effects regressions using a 1992-2002 panel of state-level data indicate that increased spending on higher education generally exhibits a relatively large negative effect on priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Equally, this result is corroborated by that of Bexheti and Mustafi (2015) in Macedonia and Trabelsi (2017). The study of Deskins et al (2019) in USA also revealed that public spending on higher education has negative effects on state employment and gross state national product while Maitra and Mukhopadhyay (2012) concluded on a negative effect Nepal. Churchill et al (2016) in their own study came to the conclusion that public educational spending has no effect on economic welfare in developing countries except in developed countries but Neil (2018) held that it has no effect on growth OECD countries but negative in developing countries.…”
Section: Negative and No Effects Of Public Educational Expenditure On Economic Welfarementioning
confidence: 99%
“…Equally, this result is corroborated by that of Bexheti and Mustafi (2015) in Macedonia and Trabelsi (2017). The study of Deskins et al (2019) in USA also revealed that public spending on higher education has negative effects on state employment and gross state national product while Maitra and Mukhopadhyay (2012) concluded on a negative effect Nepal. Churchill et al (2016) in their own study came to the conclusion that public educational spending has no effect on economic welfare in developing countries except in developed countries but Neil (2018) held that it has no effect on growth OECD countries but negative in developing countries.…”
Section: Negative and No Effects Of Public Educational Expenditure On Economic Welfarementioning
confidence: 99%
“…For instance, studies that focus on the locational model—that is, on government policies that can affect the location decisions of business and industry—investigate the effect of tax incentives and government expenditures on economic growth (e.g., Brulhart and Schmidheiny, 2015; Crain and Lee, 1999; Poulson and Kaplan, 2008; Prillaman and Meier, 2014). In contrast to this, some studies focus considerable attention on how human–capital development policies, such as education, job training, and health programs impact state economic growth (e.g., Deskins et al., 2010; Feiock, 1999; Murphy and Topel, 2016). Economic growth can also be explained within policy, management, and political boundaries.…”
Section: The Federal Government’s Functional Responsibility In Redistmentioning
confidence: 99%
“…Bensi, Black, and Dowd () are able to find a positive relationship, but only when they calculate growth and spending relative to the U.S. average. Deskins, Hill, and Ullrich () demonstrate that the problem may be due to aggregation; by separating K‐12 spending from that for higher education, they find that negative growth effects can be attributed to spending on higher education, whereas K‐12 spending exhibits no influence.…”
Section: Literaturementioning
confidence: 99%